Preparation, Characterization and Electromagnetic Interference Shielding Effectiveness Of Ppy-Pva and Ppy-Cmc Conducting Polymer Composite Films - Ekramul Mahmud, H. N. M. (2006)
Polypyrrole-poly(viny1 alcohol) (PPy-PVA) and polypyrrole-carboxymethyl cellulose (PPy-CMC) conducting polymer composite films were electrochemically prepared on Indium Tin Oxide (ITO) glass electrode from an aqueous solution containing pyrrole monomer, p-toluene sulfonate dopant and poly(viny1 alcohol)/carboxymethyl cellulose insulating polymer. The PPy-PVA and PPy- CMC composite films prepared from different process conditions were characterized by Fourier Transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD) analysis, optical microscopy, dynamic mechanical analysis (DMA), and conductivity measurement. The highest conductivity of 64 Slcm measured at room temperature was shown by PPy-PVA composite film prepared fiom 0.2 M pyrrole, 0.1 M p-toluene sulfonate and 12 x lo4 M PVA at 1.2 volt (vsSCE) among all the PPY-PVA composite films produced. The PPy-CMC composite film prepared from 0.3 M pyrrole, 0.1 M p-toluene sulfonate and 0.03 M CMC at 1.2 volt (vs SCE) showed the highest conductivity of 38 Slcm among all the PPy-CMC composite films produced. The FT-IR study of PPy-PVA and PPy- CMC composite films shows the evidence of the incorporation of PVA and CMC in PPy structure forming PPy-PVA and PPy-CMC composite films, respectively. The conductivity data of PPy-PVA shows that with the increase in PVA concentration in the pyrrole solution, the conductivity of the prepared PPy-PVA film is increasing up to certain level due to the increase in conjugation length and later it is decreasing with further increase in PVA concentration, which is again linked with the conjugation length decrease. This is supported by the FT-IR band intensity of Ic=c/Ic-N. The FT-IR study of PPy-CMC composite films shows that with the increase in CMC concentration from 0.005 M to 0.01 M, the conductivity first decreased and later with further increase in CMC concentration the conductivity showed an increasing trend and finally at 0.04 M CMC, the conductivity dropped. The DMA results of PPy-PVA and PPy-CMC composite films show the enhanced mechanical properties of both the composite films over PPy films without PVA or CMC. The storage moduli of both the composite films were found much higher than the PPy film prepared without PVA or CMC indicating that PPy-PVA and PPy-CMC composite films are much stiffer than PPy films. The gradual decrease of storage moduli of both the composite films with the increase in temperature ranging from 25 "C to 250 "C suggests that the composite films have got flexibility in their chains and thus the chains are soft. On the other hand, the storage modulus of PPy film only without PVA or CMC shows no decreasing tendency with the increase in temperature ranging from 25 "C to 250 "C indicating that the PPy film is very hard and have got no flexibility in its backbone chain. The XRD results of both PPy-CMC and PPy-PVA composite films show that the films are amorphous and have got very little order. The optical micrographs of PPy-CMC and PPy-PVA show the globular surface morphology. The changes in globular surface morphology with the change in process condition of the film preparation indicates that the process parameters used to prepare the composite films have got a good influence over the surface morphology. The intense polymerization reaction has been evidenced from the surface morphology of the films. The results of electromagnetic interference (EMI) shielding effectiveness in the microwave range of 8-12 GHz show that the highest shielding effectiveness of 45.67 dB measured in the microwave range of 8-12 GHz corresponds to the total attenuation of 99.4 % of microwave energy has been exhibited by the Pe-PVA composite film prepared from 0.2 M pyrrole, 0.1 M p-toluene sulfonate and 12 x 10" M PVA at 1.2 volt (vs SCE) among all the PPy-PVA composite films prepared. The highest shielding effectiveness of 35.7 dB measured in the microwave range corresponds to the total attenuation of 98.32 % of microwave energy has been exhibited by the PPy-CMC composite film prepared fiom 0.3 M pyrrole, 0.1 M p-toluene sulfonate and 0.03 M CMC at 1.2 volt (vs SCE) among all the PPy-CMC composite films prepared. Thus, the promise of finding any electromagnetic interference (EMI) shielding applications in the microwave frequency range lies in PPy-PVA and PPy-CMC conducting polymer composite films.